1 - Can the Bologna Process Make the Move Faster towards the Development of an International Space for Higher Education where Africa would find its place? - Jean-Émile Charlier; Sarah Croché (Journal of Higher Education in Africa, 2009)
The Bologna Process is presented to the political and academic officials of Southern countries as the bearer of form constraints – the division of higher education studies into three main cycles (a bachelor’s, master’s and doctorate degree in respectively three, five, and eight years after the completion of upper secondary education) – and the calculation of the relative importance of subjects according to a credit mechanism. As unmenacing as it may look to decision-makers, reality is more complex. Form constraints soon turn into structural constraints that are only gradually revealed – mobility implies the transnational harmonization of academic timetables, the division of teachings and assessments into semesters, etc. The implementation of the ‘Bologna spirit’ also calls for interdependent universities whereas previously each only had to comply with their national constraints. In Africa, this interdependence is a strong asset for academic officials when they have to negotiate with their authorities. As it was the case in Europe, the solution to national problems will probably entail striking international agreements whose binding force will derive precisely from their international character. Functional interdependence may enhance dialogue between academic officials. African universities should seize the opportunity of the call for dialogue as ex- pressed during the London summit in 2007 to have their qualifications certified according to international standards and thus weigh on the definition of quality that will bind the international space for higher education in the near future.